A multi-approach monitoring of particulate matter, metals and PAHs in an urban street canyon - De Nicola, Flavia; Murena, Fabio; Costagliola, M. Antonietta; Alfani, Anna; Baldantoni, Daniela; Prati, M. Vittoria; Sessa, Ludovica; Spagnuolo, Valeria; Giordano, Simonetta (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2013)
For the first time until now, the results from a prediction model (Atmospheric Dispersion Modelling System (ADMS)-Road) of pollutant dispersion in a street canyon were compared to the results obtained from biomonitors. In particular, the instrumental monitoring of particulate matter (PM10) and the biomonitoring of 14 polycyclic aromatic hydrocarbons (PAHs) and 11 metals by Quercus ilex leaves and Hypnum cupressiforme moss bags, acting as long- and short-term accumulators, respectively, were carried out. For both PAHs and metals, similar bioaccumulation trends were observed, with higher concentrations in biomonitors exposed at the leeward canyon side, affected by primary air vortex. The major pollutant accumulation at the leeward side was also predicted by the ADMS-Road model, on the basis of the prevailing wind direction that determines different exposure of the street canyon sides to pollutants emitted by vehicular traffic. A clear vertical (3, 6 and 9 m) distribution gradient of pollutants was not observed, so that both the model and biomonitoring results suggested that local air turbulences in the street canyon could contribute to uniform pollutant distribution at different heights.
The following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Holm oak leaves; metals; Moss bags; Naples urban area; PAHs; Pollutant dispersion model

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism